Multiple Criteria Decision Analysis of Quality of Institutions for European Countries in the Years 2000-2013 - Adam P. Balcerzak; Michal Bernard Pietrzak (Institute of Economic Research (IER), 2016)
The article concentrates on the problem of quality of institutions in European Union countries in the context of their compatibility with the global knowledge-based economy. The main objective of the article is to evaluate the progress obtained in that field by New Member States of the European Union in the years 2000-2013. The empirical research is based on the following hypothesis: the integration process of Central European countries with the European Union has influenced the acceleration of changes leading to improvement in the quality of their institutional systems in the context of global knowledge-based economy. The first part of the paper presents the most important determinants of the ability of a country to utilize the potential of the knowledge-based economy. This analysis is conducted on the basis of institutional economics specifically transaction cost theory. In the empirical part multiple criteria decision analysis methodology (MCDA) (the modified TOPSIS method) is applied. Data from Fraser Institute data base for Economic Freedom of the World Report has been used. The empirical research is the source of significant arguments in favor of the hypothesis of the paper.
Keywords: C38; D02; O38; 330; institutional economics; quality of institutions; transaction cost theory; global knowledge-based economy; multiple criteria decision analysis (MCDA); TOPSIS; EU